STUDENTS’ PERSPECTIVES ON THE INDEPENDENT LEARNING STRATEGY - Loisa Tambun; Neni Afrida Sari Harahap; Karunia Devi Frida (Universitas Negeri Medan, 2025)
This study addresses the gap in understanding how collaborative learning strategies support independent learning among high school students, specifically at SMA Negeri 7 Medan. The purpose of the research was to explore students’ perceptions of collaborative learning within the context of independent English language learning. A qualitative case study design was employed to gain an in-depth understanding of students’ experiences. Data were collected through an online questionnaire distributed via Google Forms, which included both closed-ended and open-ended questions to capture students’ attitudes, challenges, and personal insights. The participants consisted of Senior High School students actively engaged in collaborative learning activities. Data were analyzed descriptively to identify key themes and patterns in students’ responses. The findings reveal that students generally perceive collaborative learning as beneficial, enhancing their academic understanding, self-confidence, and communication skills while fostering social interaction and cooperation. However, challenges such as uneven participation and insufficient teacher facilitation were also noted. These results suggest that integrating collaborative strategies within independent learning can improve student engagement and outcomes if supported by effective instructional design. The study implies that educators should balance individual autonomy with structured collaboration to maximize learning benefits and recommends further research on teacher roles and cross-subject applications of collaborative learning.